Difference of preventing effects of G-CSF according to age in patients with malignant lymphoma: A nation-wide analysis in Japan. Issue 8 (August 2021) - Matsuda, Kensuke; Jo, Taisuke; Miyauchi, Masashi; Toyama, Kazuhiro; Nakazaki, Kumi; Matsui, Hiroki; Fushimi, Kiyohide; Yasunaga, Hideo; Kurokawa, Mineo
Abstract: Introduction: There has been no comprehensive analysis of the age-specific efficacy of G-CSF to prevent febrile neutropenia (FN). We evaluated factors associated with FN occurrence according to patient age in rituximab-cyclophosphamide-doxorubicin-vincristine-prednisolone (R–CHOP) treatment. Methods: We retrospectively reviewed diffuse large B-cell lymphoma (DLBCL) patients aged ≥50 years, who underwent the first R–CHOP cycle between July 2010 and March 2017, using a Japanese inpatient database. Multivariable logistic regression analysis was performed to identify the factors associated with FN. Results: A total of 16, 399 patients with untreated DLBCL were identified. Primary prophylaxis with pegfilgrastim was significantly associated with the lower occurrence of FN (odds ratio: 0.71 [95% confidence interval: 0.51–0.99]). Subgroup analysis according to age was then performed. Although there was no significance, primary prophylaxis with pegfilgrastim tended to have a lower odds ratio for the occurrence of FN in patients aged 50–60 years (0.86 [0.39–1.89]) and 61–70 years (0.64 [0.36–1.13]). In patients aged 71–80 years, primary prophylaxis with pegfilgrastim was significantly associated with reduced FN occurrence (0.46 [0.26–0.80]). Notably, in patients aged >80 years, the use of pegfilgrastim tended to be associated with a rather higher occurrence of FN (1.55 [0.84–2.87]). Conclusions: Preventing effect of G-CSF may be limited in patients aged >80 years.